Distinct Domains of αIIbβ3 Support Different Aspects of Outside-In Signal Transduction and Platelet Activation Induced by LSARLAF, an αIIbβ3 Interacting Peptide - Derrick, Jerry M.; Shattil, Sanford J.; Poncz, Mortimer; Gruppo, Ralph A.; Gartner, Kent T. (Thrombosis and Haemostasis, 2001)
The peptide LSARLAF causes αIIbβ3-dependent platelet activation exemplified by secretion, aggregation, spreading and adhesion on fibrinogen, and tyrosine phosphorylation. αIIbβ3-dependent outside-in signal transduction induced by LSARLAF was investigated in variant thrombasthenic platelets which lack most of the cytoplasmic domain of the integrin β3 subunit (αIIbβ3 Δ724). These studies revealed that only certain aspects of this αIIbβ3-dependent outside-in signaling were affected by the β3 truncation. Specifically, αIIbβ3 724 supported LSARLAF-induced platelet aggregation, agglutination and secretion, but failed to trigger cytoskeletal reorganization and platelet spreading on fibrinogen, despite the fact that PMA-induced non αIIbβ3 mediated signaling caused spreading of these platelets on fibrinogen. Thus, distinct domains of αIIbβ3 are required to support different aspects of LSARLAF-induced platelet activation. Furthermore, these studies suggest that not all αIIbβ3-dependent platelet responses require an intact β3 cytoplasmic tail.
Keywords: Outside-in signaling; platelet spreading; tyrosine phosphorylation